CYP1A2 activity, gender and smoking, as variables influencing the toxicity of caffeine - CARRILLO, JUAN A.; BENITEZ, JULIO (British journal of clinical pharmacology, 1996)
We have investigated several factors that might be related to the occurrence of toxic effects during the performance of a urinary test with caffeine (300 mg p.o), in 120 healthy volunteers. A total of 218 toxic effects were self‐reported by eighty‐two (68%) subjects. Females and nonsmokers were at the highest risk (chi‐square test, P=0.01). Furthermore, two nonsmoking females experienced a symptomatology with delirium, restlessness, muscle tremor, vomiting and wakefulness. Among females and nonsmokers, those subjects who experienced toxic effects had lower caffeine N3‐demethylation index (CYP1A2 activity) compared with unaffected females (1.87±0.51 vs 1.47±0.27, P<0.0005) and nonsmokers (1.69±0.23 vs 1.49±0.31, P<0.02). Caffeine N1‐ and N7‐demethylations indices were also lower among females (P<0.0005) and nonsmokers (P<0.02) who reported toxic symptoms. We conclude that CYP1A2 activity, gender and smoking are variables to be considered as influencing the toxicity of caffeine.